Glyphosate on shikimic acid on Urochloa plantaginea - Almeida,Sydnei Dionisio Batista de (2020)
ABSTRACT: Shikimic acid (SA) has witnessed a strong increase in recent years due to the increasing demand of the pharmaceutical and cosmetic industry. The SA is used as a precursor for the synthesis of oseltamivir phosphate (Tamiflu®), a potent viral inhibitor and is extracted from the plant Illicium verum Hook which has a limited availability. This article proposed the use of Urochloa plantaginea (Link.) webster and glyphosate, as an alternative source of SA. U. plantaginea plants with 3 - 4 tillers and 4 - 6 leaves were harvest at 3, 6, 9 and 12 days after application (DAT) of low rates of glyphosate. Samples were dried, extracted, analyzed by HPLC and LC-MS/MS. The maximum SA concentrations were observed at 6 days after glyphosate at 36 g.a.e.ha-1 was applied in plants of U. plantaginea with 4 to 6 leaves. The capability of this annual gramineae to produce elevated SA levels throughout the entire biomass affords its potential for a greater yield on a per hectare basis.